PENGGEMUKAN KEPITING BAKAU Scylla serrata BERUKURAN KECIL HASIL TANGKAPAN NELAYAN DI DUSUN WAEL, KECAMATAN PIRU, KABUPATEN SERAM BAGIAN BARAT - Yuliana Natan (Jurnal Perikanan Universitas Gadjah Mada, 2014)
Experiment on the enlargement of individual mud crab Scylla serrata which caught by ﬁsherman in the waters of Wael District still under economy worthy price. The purposes of this study is to see the crab growth rate through one of the crab ﬁ sheries management strategies, there are maintenance and fattening. The weight size of individual mud crab used in this study between 100 gr to 325 gr ind-1. Male mud crabs was separated from females as a fattening treatment experiment and was placed on the two bamboo cages which each contain of 15 individuals then placed separately. Observation was made along 4 months. The result showed that the growth pattern of male and female mud crabs is still exponential, which male individu reach on average 532.3 gr weight change ind-1 and female with 499 gr ind-1 in 4 months. It concluded that female mud crabs has slower growth rate than males, and the fattening not reached an asymptotic value, which means they still can be fattened again in the cage.